Mammalian Atg2 proteins are essential for autophagosome formation and important for regulation of size and distribution of lipid droplets - Velikkakath, Anoop Kumar G.; Nishimura, Taki; Oita, Eiko; Ishihara, Naotada; Mizushima, Noboru (Molecular biology of the cell, 2012)
Macroautophagy is an intracellular degradation system by which cytoplasmic materials are enclosed by the autophagosome and delivered to the lysosome. Autophagosome formation is considered to take place on the endoplasmic reticulum and involves functions of autophagy-related (Atg) proteins. Here, we report the identification and characterization of mammalian Atg2 homologues Atg2A and Atg2B. Simultaneous silencing of Atg2A and Atg2B causes a block in autophagic flux and accumulation of unclosed autophagic structures containing most Atg proteins. Atg2A localizes on the autophagic membrane, as well as on the surface of lipid droplets. The Atg2A region containing amino acids 1723–1829, which shows relatively high conservation among species, is required for localization to both the autophagic membrane and lipid droplet and is also essential for autophagy. Depletion of both Atg2A and Atg2B causes clustering of enlarged lipid droplets in an autophagy-independent manner. These data suggest that mammalian Atg2 proteins function both in autophagosome formation and regulation of lipid droplet morphology and dispersion.